Pedagogical residency and teacher training in times of pandemic: challenges and perspectives from the perspective of undergraduates (Research, Society and Development, 2021)
The research sought to understand the perceptions of residents linked to the Pedagogical Residency Program (PRP) within the scope of the Federal Institute of Piauí (IFPI), with impact on the impacts of implementing the program in a remote setting. The research is characterized as basic, observational in nature and quali-quantitative approach. It is fully carried out online, using digital communication tools to contact residents. The formalization of participation occurs through the acceptance of a Free and Informed Consent Form (TCLE). For data collection, we used a semi-structured questionnaire prepared through the Google Forms platform and sent to participants through the WhatsApp application. The answers to the answers show that the PRP-IFPI (2020-2022) is very important for the professional training of residents, and that despite the requirements imposed by remote learning, its implementation has been taking place in an adequate manner and providing diverse learning. Residents also point out as difficulties of basic education students in accessing digital technologies and the internet, as well as the frequent lack of interest and little participation in synchronous classes. The combination of these points with the delicate moment experienced may also be directly affecting the residents' well-being, as most of them associate feelings of ruins with remote education and feel sadder in the current moment compared to the period before the pandemic. Thus, we highlight the need for studies that seek to understand the perceptions of different participants in remote education, as well as the impact of this period on the teaching and well-being of teachers and students.